Facilitating Physics Problem-Solving Skills with Geometry Optics E-Module Flipbook View: A Reliability Test - Ima Puspita Rukmi; Sindy Chintyawati; Bayu Setiaji (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2022)
Students' physics problem-solving skill is still low, especially in physics problems related to everyday life, not simple quantitative problems. This is because the learning modules used today still do not invite students to solve real problems around them related to physics. This study aims to test the feasibility of the E-Module with a flipbook view which was developed to improve students' problem-solving skills on the material of reflection and refraction of light. The research method used is Research and Development (R&D) with a 4-D development model. The stages of E-Module development in this research are only the define, design, and development stages. The research instrument was in the form of an E-Module feasibility test questionnaire via google form which was tested by 50 prospective physics teacher students. The results showed that the feasibility level of the developed E-Module was within the very feasible criteria. Thus, the developed E-Module is very feasible to improve students' problem-solving skills and can proceed to the broad trial stages.